Trip Rate Model of Attraction in Higher Education Zone - Abied Rizky Putra Muttaqien; Yudi Basuki (JACEE (Journal of Advanced Civil and Environmental Engineering), 2020)
Land use and transportation have a very close relationship. As the first stage in the four-step trip demand model that trip generation can explain the relationship between the two variables. In the analysis of trip generation and attraction it can be predicted how many movements result from a certain land use. One of the land uses that have a fairly high number of perch is in the higher education zone. Sultan Agung Islamic University (Unissula) Semarang is a campus located on Jalan Kaligawe km. 4. The rise arising from the existence of the tertiary education area is a high enough tourist attraction, causing problems such as traffic jams and traffic accidents during busy times morning and evening. This study aims to analyze the trip generation of Unissula Semarang higher education which has a total building area of 102,754.40 m2 with activities in and out of vehicles both two-wheeled and four-wheeled from morning to evening. The approach used in this research is quantitative descriptive. The analytical method used is trip-rate analysis. The results of this study indicate that vehicles entering the type of car experience peak hours at 08.00 - 08.30 as many as 210 pcu / hour while motorbikes at 07.30 - 08.00 as many as 94 pcu / hour. However, cumulatively, the highest trip rate occurred at 07.30-08.00. in the amount of 0.3 pcu / hour. While the provisions of the Institute of Transportation Engineers (ITE) states that the trip rate for tertiary institutions is 0.11 pcu / hour. Thus the need for efforts to distribute vehicles so that the traffic volume density can be decomposed.